Antitumor activity of PAbs generated by immunization with a novel HER3-targeting protein-based vaccine candidate in preclinical models - Bermúdez-Abreut, Ernesto; Bergado Báez, Gretchen; Martínez Pestano, Melissa; Attanasio, Giuseppe; Gonzales Castillo, Carlos Yordan; Hernández Fernández, Diana Rosa; Alvarez-Arzola, Rydell; Alimonti, Andrea; Sánchez-Ramírez, Belinda (Frontiers in Oncology, 2024)
Despite the cumulative evidence supporting HER3 as a target for antitumor therapies, no agents targeting HER3 have been approved for cancer treatment. Most of the agents evaluated in preclinical and clinical trials have been specific monoclonal antibodies (MAbs), with few examples of active immunotherapy directed against this receptor. However, some cancer vaccine formats may generate polyclonal antibodies (PAbs) that replicate the diverse effector mechanisms of MAbs, including ligand neutralization and receptor degradation. In this study, we developed a protein subunit-based monovalent vaccine candidate targeting the extracellular domain (ECD) of HER3. Immunization of mice with a formulation targeting murine ErbB3-ECD successfully overcome tolerance to this self-antigen, inducing high titers of ErbB3-specific PAbs. The antitumor potential of this formulation and the induced PAbs was demonstrated in vivo and in vitro in an ErbB3-overexpressing 3LL-D122-derived tumor model. The immunogenicity of the HER3-ECD-based vaccine candidate was confirmed by the induction of high titers of HER3-specific PAbs. Consistent with the initial results, HER3-ECD-targeting PAbs were cytotoxic in several human epithelial tumor cell lines and exerted antitumor effects in vivo. These results support the value of HER3 as a tumor antigen and the effector mechanisms of HER3-specific therapeutic MAbs, while suggesting the potential of the proposed vaccine candidate for the treatment of HER3-expressing carcinomas.